The Changes Of Product Structure In Islamic Banking: Case Study Of Malaysia. - Bahari, Zakaria (2009)
Malaysia is aggressively developing its Islamic financial system to becoming an international Islamic financial hub. One of all Islamic financial system segments is Islamic banking sector.